Social networks and innovation strategies in knowledge-intensive services: the case of software - Salavisa, I. (2018)
This paper deals with the role of social networks in the innovation strategies of the software for telecommunications sector; although a relatively small segment in the global software industry, this is one of the most innovative. In fact, its products address the demand of the sophisticated and fast changing telecommunications industry, with mobile communications at its core. The literature has stressed the relevance of social networks for the innovative process of knowledge-intensive firms. Most of these firms, and particularly small and medium sized firms, depend on external resources to complement their built-in capabilities, partly accessed via non-market means. As a consequence, networks have become increasingly crucial for the access to these resources, which are quite diversified. Most of the extant studies deal with aggregate networks; however, the diversity of resources is expected to affect the forms of access, and therefore the configurations of social networks. In this paper we study disaggregated social networks in two groups of firms, more radical innovators vis-à-vis incremental innovators, according to the type of resource being accessed i.e. technological knowledge and complementary assets. Technological knowledge has become complex, fast changing and distributed among various players. In the case of software, firms have to interact not only with other domestic and multinational firms in the same sector and universities, but also with customers; the latter are considered a major source of innovation. Complementary assets such as capital, information on potential opportunities, access to markets and highly skilled personnel have become more specialized and sophisticated. Such resources are not totally obtainable through anonymous and stand-alone market transactions. Their access requires interaction, information exchange and very often trust. Drawing on original information collected through a detailed questionnaire, we analysed a set of 29 firms producing software for telecommunications in Portugal, split into two sub-sets according to the range of innovation (more radical vs. more incremental). We looked for the main factors related to the configuration of the networks developed (composition, structure, size, number of components) to explain the differences in the innovation strategies adopted by the two groups of companies. Results confirm the existence of contrasting network configurations of radical versus incremental innovators and the value of a fine-grained approach. Our approach can therefore contribute to the debate on the most favourable network configuration for innovation: this depends not only on the range of innovation but also on the resource that is exchanged through the relation.